Dampak Toxic Parents Terhadap Karakter dan Moral Anak - M. Safardi Bugi; Titus Gaite; Jumiati Tuharea (Peneliti.net, 2023)
Toxic parents are parents' behavior that always curbs and verbally and nonverbally hurts children, indirectly parents will make the distance with children disharmonious. The purpose of this study is to (1) determine the impact of Toxic Parents on children's character and moral development. (2) To find out efforts to prevent parents who are toxic to children. The research method used in this study is Qualitative Research, namely by using or describing an event systematically, factually and accurately regarding the facts or phenomena investigated. The results showed (1) The impact of Toxic parents for children lies in their mentality which can cause trauma because the parenting pattern of parents who always force their children to follow their will (2) Lack of efforts made by families to avoid toxic behavior to children should be the main pillars that have an important role in child development that can shape the child's personality.